Self-control and impulsiveness in adult humans when food is the reinforcer - Logue, A W; King, G R (Appetite, 1991)
Moderately food- and water-deprived women repeatedly chose between longer access to juice after a long delay (the self-control alternative), and shorter access to juice after a short delay (the impulsive alternative). In contrast to previous experiments using points exchangeable for money as the reinforcer, which have found consistent self-control across subjects, behavior of the present subjects varied between complete self-control and complete impulsiveness. Individual subjects' degree of self-control was not related to their majors, to their past or present degree of reported actual food deprivation, to their ratings of desire for the juice, or to their latency to respond. However, subjects who reported that they were currently dieting were significantly more impulsive; they obtained juice earlier within individual trials but had smaller total juice access time. The operant conditioning laboratory paradigm developed for the present research can be useful in investigating general determinants of self-control and impulsiveness for food reinforcers, as well as in investigating the origins of individual differences in food choice.